Electronic journal of biotechnology : EJB - Universidad Católica de Valparaíso; Chile. Comisión Nacional de Investigación Científica y Tecnológica (Universidad Católica de Valparaíso and CONICYT, 1997)
International scientific electronic journal covering all areas related to biotechnology, from molecular biology and the chemistry of biological process to aquatic and earth environmental aspects, as well as computational applications and policy issues.
Keywords: Biotechnology : Periodicals; Biotechnology : Research : Periodicals; Bioengineering : Periodicals; Biotechnology; Biotechnologie : Périodiques; Biotechnologie : Recherche : Périodiques; Biotechnologie; bioengineering; Biotechnology; Bioengineering; Biotechnology : Research